Methods of estimation of effectiveness of various types of indicators application in airborne means of information display - Зубарев, В. В.; Мокрицкий, В. А.; Поляруш, О. В.; Перегудов, А. Н.; Савельев, А. А. (Proceedings of National Aviation University (archive), 1999)
Considered are features of modern microelectronic means of information display which are the most effective for airborne equipment use. Carried out is comparative analysis of their properties and features, mainly the information capacity, speed of response, reliability, coefficient of readiness, ergonomity, efficiency. Presented is a wide data base of various construction versions of indicators